Output-Based Aid in Mali Rural Electrification Hybrid System Project - World Bank (2015)
Electrification can be a significant driver for improving livelihoods in rural communities. In rural Mali, where more than 80 percent of the country’s population lives, the electrification rate is only 15 percent. Increasing access to electricity in rural Mali is crucial for economic development, social cohesion, and reconstruction following the country’s recent period of conflict, political instability, and food insecurity. This note discusses an innovative output-based aid (OBA) project in rural Mali, the first such project in the energy sector to support development of mini-grids on a large scale. The project complements an innovative hybrid-system model supported by the International Development Association (IDA) and climate investment funds and scaling up renewable energy in low income countries program (SREP) to expand rural access to modern energy services and increase renewable generation.